SERVICE FINDER: An Android-based Service Finding and Booking Application - FOO, KELLY YEN LI; Norfaradilla Wahid (Applied Information Technology And Computer Science, 2023)
Service Finder is an online service finding and booking Android application developed to ease the public to find the local services such as plumbing and electrical efficiently. Service Finder allows users to search for the service nearby by using the location-based service approach. Location-based services use the global satellite positioning to access the location of the user to provide specific information to the user. Service Finder is developed based on system prototyping methodology by using Android Studio and MySQL database. Android Studio is software used to develop Android applications while MySQL database is a database used to store data of the application. Service Finder includes five modules which are management on profile, account, service, appointment and rate and review. Service Finder allows users to find service needed according to their location and make appointments with preferred time. Overall testing on the developed application is passed except for rate modules.